Why do Firms Change Their Dividend Policy? - Ali, Ijaz; Gohar, Ali; Meharzi, Omar (International Journal of Economics and Financial Issues, 2017)
Prior literature has largely documented managers' preference of sticking to their dividend policy. This perceived inflexibility of managers makes a dividend policy switch an important milestone in a firm's life. Blau and Fuller (2008) state that existing theories do not help understand why some firms never pay dividends, while others consistently pay them. This paper examines the factors that motivate managers to change their long term dividend policy. By employing univariate and multivariate tests and propensity score matching method, the authors provide empirical evidence consistent with the life cycle theory of dividends and Litner's proposition, and inconsistent with the signaling theory of dividends. Unlike previous studies, by investigating the characteristics of dividend policy switchers, this study examines factors affecting firms' long term dividend policy. In addition, by analyzing both positive and negative switchers, this study helps to determine whether the same factors are responsible for dividend abandonments and initiations. Keywords: Dividend policy, signaling theory of dividends, life cycle theory of dividends JEL Classification: G35